Legacy and Emerging Contaminants in Demersal Fish Species from Southern Norway and Implications for Food Safety - Marco Parolini; Sara Panseri; Federico Håland Gaeta; Federica Ceriani; Beatrice De Felice; Maria Nobile; Giacomo Mosconi; Trond Rafoss; Francesco Arioli; Luca Maria Chiesa (Foods, 2020)
The present study aimed at measuring the levels of legacy and emerging contaminants in fillet samples from four demersal fish caught in two fishing sites from Southern Norway, in order to assess possible implications for food safety. Levels of organochlorine compounds (OCs), organophosphate pesticides (OPs), polychlorinated biphenyls (PCBs), polybromodiphenyl ethers (PBDE), per- and polyfluoroalkyl substances (PFASs), and polycyclic aromatic hydrocarbons (PAHs) were measured in fillet from Atlantic cod (Gadus morhua), European plaice (Pleuronectes platessa), lemon sole (Microstomus kitt), and European flounder (Platichthys flesus) specimens. A negligible contamination by all the investigated chemicals was noted in both the fishing sites, as very low levels of OCs, PCBs, and PFASs were noted in a limited number of individuals for each species. Considering the levels of contaminants measured in fillets of the four demersal fish species, negligible risk for human health for Norwegian consumers can be supposed.